EFEKTIVITAS TRANSAKSI DIGITAL: STUDI PENGGUNAAN APLIKASI PEGADAIAN DIGITAL SERVICE DI PT. PEGADAIAN (PERSERO) UPC KEDUNGGALAR KABUPATEN NGAWI - rahayu, eka; Sari, Putri Herdiana (Commodity : Jurnal Perbankan dan Keuangan Islam, 2025)
This research aims to analyze the effectiveness of the Digital Pawnshop Service (PDS) in providing ease and benefits of transactions for customers and employees of PT. Pegadaian (Persero) UPC Kedunggalar, as well as to review its compliance with the Civil Code Article 1150. The research method used is descriptive qualitative with primary and secondary data. Data collection techniques were carried out through interviews. Data were analyzed by processing and organizing them, then breaking them down into smaller units to identify patterns and themes. The results of the study indicate that the impact of using the PDS application on transaction effectiveness and services at UPC Kedunggalar has not yet been significant and efficient.